Correlation Between Complete Blood Count Parameters with Procalcitonin in Immunogenomic Phases of COVID-19 Patients - Sellynastiti, Sarah Triwinar; Rusli, Musofa; Hernaningsih, Yetti (Indonesian Journal of Tropical and Infectious Disease, 2025)
Coronavirus Disease 2019 (COVID-19), a global pandemic caused by SARSCoV-2, presents varying degrees of severity influenced by different immunogenomic phase. The immunogenomic phase that occurs in patients with COVID-19 is divided into three phases, namely the initial phase, propagating phase, and complicating phase. Severity disease progression can be monitored from the results of complete blood count (CBC) parameters and several inflammatory parameters such as procalcitonin. The purpose of this study was to investigate, during the immunogenomic phase of COVID-19 patients, the correlation between PCT levels and full blood count parameters. Patients treated at Dr. Soetomo General Hospital for COVID-19 were the subjects of this crosssectional study. Data analysis used in this study is Kolmogorov-Smirnov Test for normality, followed by Wilcoxon signed-rank test and bivariate Pearson correlation test to determine the correlation between complete blood count (CBC) parameters and PCT. Our findings reveal that most patients are male, predominantly aged between 50 and 60 years. Distinct variation of CBC parameters and PCT levels were observed in each phase. A significant relationship between these hematological markers, the immunogenomic phase and the progression of the disease. The PCT level of COVID-19 patients was associated with parameters of red blood cells, including hemoglobin, hematocrit, and the width-standard deviation of red blood cell distribution, leukocytes and their differential count, including lymphocytes and neutrophils, and platelets.. This analysis further understanding regarding the hematological dynamics in COVID-19 patients, providing important information about the pathophysiology of the disease and potential biomarkers for monitoring its progression.